Does noninvasive follicular thyroid neoplasm with papillary‐like nuclear features have distinctive features on sonography? - Brandler, Tamar C.; Yee, Joseph; Zhou, Fang; Cho, Margaret; Cangiarella, Joan; Wei, Xiao‐Jun; Yee‐Chang, Melissa; Sun, Wei (Diagnostic cytopathology, 2018)
Background The noninvasive encapsulated follicular variant of papillary carcinoma (nEFVPTC) has recently been reclassified to “noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP),” removing this entity from the malignant category. This re‐categorization has had major implications for clinical management. NIFTP has overlapping cytohistologic features with papillary thyroid carcinoma (PTC) and with follicular adenomas (FA), but sonographic data comparing NIFTP to PTC and FA is lacking. Our study examines the sonographic features of NIFTP as compared with PTC and FA. Methods Ultrasound scans and Doppler blood flow from subjects who had pre‐surgical sonograms and fine needle aspiration biopsies with final surgical pathology diagnoses of NIFTP/nEFVPTC, classical PTC, and FA between 01/2013‐08/2016 were assessed. Sonographic and Doppler features as well as Bethesda System (TBS) diagnoses were recorded and analyzed. Results 40 NIFTP, 58 classical PTC, and 23 FA cases were included. The most common NIFTP pre‐surgical TBS cytology diagnosis was Atypia of Undetermined Significance (AUS/FLUS) (40%). NIFTP cases predominantly displayed wider‐than‐tall shape (100%), smooth borders (75%), occurrence in multinodular glands (82.5%), heterogeneous echogenicity (50%), both perinodular and intranodular Doppler flow patterns (70%), minimal Doppler flow grade (62.5%), and no calcifications (90%). Conclusions Our study demonstrates that NIFTP, PTC, and FA display several distinguishing and overlapping sonographic and Doppler features. Sonographic features appear to complement cytology findings and may help raise pre‐operative concern for NIFTP in the proper clinical setting, potentially leading to a more conservative management approach.